Phonetics and phonology of soft 'g' in Turkish. (14th August 2017) - Ünal-Logacev, Özlem; Żygis, Marzena; Fuchs, Susanne
Abstract : The present study aims to approach soft 'g', a highly disputable sound in Turkish phonetics and phonology, from a multidimensional perspective by (i) analysing its historical development, (ii) investigating its distribution in a dictionary of Modern Turkish, and (iii) studying its acoustic realization. In the Ottoman script soft 'g' was represented with two letters: <غ>, pronounced [ɣ], was used in the context of preceding back vowels Vback _(Vback, C); <گ>, pronounced [j ], was used in the context of preceding front vowels Vfront _(Vfront, C). In 1928, due to a reform in orthography, these two vocalic contexts were obscured by replacing both <غ> and <گ> with <ğ>. Our investigation of the distribution of /ğ/ in the native vocabulary of Modern Turkish reveals that /ğ/ is in complementary distribution with /ɡ/: /ğ/ appears word-finally and word-medially (i.e. syllable-finally Vğ.C and intervocalically V.ğV), while /ɡ/ is found word-initially and word-medially (i.e. syllable-initially when following a consonant C.ğV). However, in loan words which are well assimilated into Turkish by means of phono-morphological rules the complementary distribution is not attested. Moreover, the behavior of soft 'g' in phonological processes strongly suggests that the sound is part of the phonemic inventory of Turkish. Finally, the results of our two acoustic experiments show that /ğ/ is phonetically manifested in the lengthening of the preceding vowel (/Vğ/ → [Vː]) independently of the surrounding vowel environment, word position, and participant age. In addition, the results indicate that speakers of Modern Turkish do not realize acoustic properties of a velar gesture.